Defining the weights of the EFQM excellence model criteria for different business sectors - a multicriteria approach. (7th October 2020) - Politis, Yannis; Grigoroudis, Evangelos
EFQM model is Europe's most prestigious award for organisational business excellence given to the best performing organisations in Europe. The aim of this paper is to propose a multicriteria approach to assess the weights of the model's criteria based on the specific needs of different business sectors. For this reason a two stage process is proposed. In the first stage, criteria weights are assessed according to the rankings of a set of organisations with different scores on the EFQM excellence model criteria given by business experts from specific sectors or and participants of the quality award. The second stage concerns modifications and additional information or restrictions given by EFQM experts in order to improve the robustness of the preference model estimated from the previous stage. Considering that little can be found in literature concerning a general methodology for the construction of sector specific models, the paper proposes a general approach to adjust the weights of the EFQM model criteria to better fit the specific needs of different business sectors.